Synthesis of Bandgap‐tunable Transition Metal Sulfides through Gas‐phase Cation Exchange‐induced Topological Transformation. Issue 18 (24th March 2023) - Da, Pengfei; Zheng, Yao; Hu, Yang; Wu, Zelong; Zhao, Hongyu; Wei, Yicheng; Guo, Linchuan; Wang, Jingjing; Wei, Yanping; Xi, Shibo; Yan, Chun‐Hua; Xi, Pinxian
Abstract: Oriented synthesis of transition metal sulfides (TMSs) with controlled compositions and crystal structures has long been promising for electronic devices and energy applications. Liquid‐phase cation exchange (LCE) is a well‐studied route by varying the compositions. However, achieving crystal structure selectivity is still a great challenge. Here, we demonstrate gas‐phase cation exchange (GCE), which can induce a specific topological transformation (TT), for the synthesis of versatile TMSs with identified cubic or hexagonal crystal structures. The parallel six‐sided subunit (PSS), a new descriptor, is defined to describe the substitution of cations and the transition of the anion sublattice. Under this principle, the band gap of targeted TMSs can be tailored. Using the photocatalytic hydrogen evolution as an example, the optimal hydrogen evolution rate of a zinc‐cadmium sulfide (ZCS4) is determined to be 11.59 mmol h −1  g −1, showing a 36.2‐fold improvement over CdS. Abstract : The occurrence of cation exchange with different crystal structures is limited. We propose a new descriptor, the parallel six‐sided subunit (PSS), to synthesize transition metal sulfides with crystal structure selectivity by gas‐phase cation exchange‐induced topological transformation. Powered by precise synthetic control, the photocatalytic hydrogen evolution performance is improved by 36.2 times after band gap engineering.